The effect of simultaneous flickering light stimulation on global form and motion perception thresholds - Braunitzer Gábor (NEUROSCIENCE LETTERS, 2014)
The question regarding the exact function of the primary visual cortex (V1) in vision has been around ever since the description of residual vision after damage to this cortical area by Riddoch in 1917. In 2002, Schoenfeld and colleagues proposed that V1 can be saturated by flashes of light, by which the function of V1-bypassing visual pathways can be"unmasked". The Schoenfeld group found that light flashes applied on stimulus onset led to the elevation of brightness increment detection thresholds, but left motion detection thresholds unaltered. Although the proposed method (i.e. the use of light flashes to induce refractoriness in V1) could be a simple, cheap and elegant way of exploring V1 functions, no study has followed up on this. Therefore it is not known if it works at all with other types of stimuli. For that reason, we decided to revisit the idea in a modified form. Global form and motion perception thresholds were assessed with static Glass pattern stimuli and random dot kinematograms, with and without 12Hz flickering light stimulation. Global motion thresholds were almost unaltered by flickering stimulation, while a significant threshold elevation was caused in the global form perception task. The strongest conclusion allowed by our data is that simultaneous flickering photostimulation elevates global form perception thresholds but not global motion perception thresholds. This is in some way related to the refractoriness generated in an unsatisfactorily defined part of V1. We suggest that this does not necessarily reflect the activity of V1-bypassing pathways, and propose that the application of light flashes is a method that deserves more attention in the exploration of the V1-dependent and independent elements of visual consciousness in human subjects.